2020
DOI: 10.3390/cancers12041037
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Selective Treatment of Cancerous and Non-Cancerous Human Cervical Cell Models by a Non-Thermally Operated Electrosurgical Argon Plasma Device

Abstract: Cold atmospheric plasma (CAP) treatment is developing as a promising option for local anti-neoplastic treatment of dysplastic lesions and early intraepithelial cancer. Currently, high-frequency electrosurgical argon plasma sources are available and well established for clinical use. In this study, we investigated the effects of treatment with a non-thermally operated electrosurgical argon plasma source, a Martin Argon Plasma Beamer System (MABS), on cell proliferation and metabolism of a tissue panel of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…With regard to cancer treatment, various strategies using different types of CAPs have recently shown promising effects in cellular tumor models of breast cancer 12 14 , cervical cancer 13 15 , liver cancer 16 , lung cancer 17 , skin cancer 18 22 , and other cancers 6 , 8 . Numerous therapeutic advantages of CAPs over treatments with conventional chemotherapeutic agents have been identified as a result of previous studies, the most important being probably the selective effect of cold plasma on normal and carcinoma cells 22 24 .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to cancer treatment, various strategies using different types of CAPs have recently shown promising effects in cellular tumor models of breast cancer 12 14 , cervical cancer 13 15 , liver cancer 16 , lung cancer 17 , skin cancer 18 22 , and other cancers 6 , 8 . Numerous therapeutic advantages of CAPs over treatments with conventional chemotherapeutic agents have been identified as a result of previous studies, the most important being probably the selective effect of cold plasma on normal and carcinoma cells 22 24 .…”
Section: Introductionmentioning
confidence: 99%
“…New therapy options are needed to treat the cancer and to reduce damage to normal tissues. For cancer-selective treatment, Feil et al [ 4 ] reported the effects of a non-thermally operated Martin Argon Plasma Beamer System (MABS) on cervical cancer cell lines and non-cancerous cervical tissue cells. Weiss et al [ 5 ] presented an electron-spin resonance spectroscopy on human tissue samples and treated with different cold atmospheric plasma (CAP) doses, allowing the distribution and the measurement of consequential radicals in the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…CAP applications in oncology have shown remarkable anticancer effects in vitro cell-lines, including, for example, melanoma [30], cutaneous squamous carcinoma [31], pancreatic [32], liver [33], gastric [34], colon [35], prostate or urinary bladder [36,37], breast [38][39][40][41][42][43][44], head and neck cancer [45], osteosarcoma [46,47], glioblastoma [48], lymphoma [49], acute myeloid leukaemia [50], multiple myeloma [51], human fibrosarcoma [52], or lung cancer [53], as well as in vivo solid tumour types in animal (mice) models, e.g., colon [54], breast [55,56], prostate cancer [57], cholangiocarcinoma [58], schwannoma [59], glioblastoma [60], or melanoma [61]. A limited number of studies have been published in oncogynaecology, however, mostly restricted to in vitro cell lines, e.g., cervical [12,[62][63][64][65][66][67][68][69], endometrial [70][71][72], or ovarian…”
Section: Introductionmentioning
confidence: 99%